INSTRUMEN DAN MEDIA DALAM LAYANAN BIMBINGAN DAN KONSELING - N NURVIYANTI (Universitas Islam Negeri Mataram, 2019)
Instrument and media in guidance and counseling services are tools used in helping a counselor or psychiatrist in resolving the problems faced by the students or individuals, until the students’ problem or individuals can be resolved soon. Nowadays, the implementation of guidance and counseling services can be said that it has run in various level of education, such as: kindergarten, elementary school, junior high school, and senior high school. Although we can say that it has run, however the implementation has not been maximal yet. Because the implementation of guidance and counseling services have not been maximal yet, the researcher was interested in discussing about the use of instrument and media in guidance and counseling services, including the instruments used are based on analysis of data and the needs of the students.